2019
DOI: 10.1210/er.2019-00085
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Debates in Adult Papillary Thyroid Cancer Management

Abstract: An ever-increasing population of patients with papillary thyroid cancer is engaging with health care systems around the world. Numerous questions about optimal management have arisen that challenge conventional paradigms. This is particularly the case for patients with low-risk disease, who comprise most new patients. At the same time, new therapies for patients with advanced disease are also being introduced, which may have the potential to prolong life. This review discusses selected controversial issues in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 203 publications
(205 reference statements)
0
46
0
Order By: Relevance
“…The current therapeutic strategies are rapidly evolving towards less aggressive treatments. Nevertheless, up to 25% of patients will develop recurrence in both locoregional and distant sites [6]. Therefore, staging system should also stratify the risk of recurrence to provide guidance for treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…The current therapeutic strategies are rapidly evolving towards less aggressive treatments. Nevertheless, up to 25% of patients will develop recurrence in both locoregional and distant sites [6]. Therefore, staging system should also stratify the risk of recurrence to provide guidance for treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…The standard therapy of near-total or total thyroidectomy was not possible due to her recurrent HGSC-O (2,3,5). Thus, she continued several chemotherapies that are far from common practice for PTC treatment (4,6). When our patient was fit for surgical intervention, her thyroid pathology revealed evidence of PTC resolution.…”
Section: Discussionmentioning
confidence: 84%
“…The biological characteristics of PTC are highly diverse, ranging from nonprogressive to invasive metastatic carcinoma. Although there are various treatment modalities available for papillary thyroid cancer, researchers are still searching for an optimal treatment [ 90 , 91 ]. Wen et al found that SBF2-AS1 expression increased distinctly in PTC cells and strongly affected tumor progression.…”
Section: Roles Of Sbf2-as1 In Diverse Cancersmentioning
confidence: 99%